Esophageal Perforation After Anterior Cervical Surgery: A Case Report and Literature Review. Issue 2 (March 2022) - Modi, Hitesh N.; Shreshtha, Utsab; Patel, Udit; Kotecha, Hardik; Patel, Mahesh D.; Dileep, Pratibha
Abstract : Summary and Background: Esophageal perforation (EP) after anterior cervical surgery is a rare but potentially life-threatening condition. EP caused by malpositioned implants in cervical spine injury with multiple comorbidities is challenging to treat simultaneously. Study: This was a case report study. Purpose of Study: The aim of this study was to present successful treatment of EP in a subluxated C5–C6 level with implant failure, infection, septicemia, and comorbidities. The aim was to emphasize the need for a multispecialty approach while treating serious complications. Case: A 72-year-old woman presented to the ER with a history of operated cervical spine a week ago and having breathlessness, fever, wound infection, and tracheostomy in situ. After primary investigations, the patient was initially treated in the intensive care unit, where bleeding from the tracheostomy site was noticed. Upon endoscopy, EP was diagnosed due to implant failure. She was operated for revision cervical spine surgery (drainage of pus with anterior and posterior cervical fixation) and percutaneous endoscopic gastrostomy tube insertion (esophageal diversion). On exploration of EP, a decision was made to perform conservative treatment as initial tag sutures did not hold due to infection. Postoperatively, the patient developed rectal bleed 3 times, which was ultimately treated with cecal bleed embolization. The infected cervical wound was managed with an open dressing. The patient was managed with intermittent assisted ventilation through tracheostomy postoperatively. Barium swallow at 10 weeks confirmed healing of EP and oral feed was started. Tracheostomy closure was performed once the wound had healed, and the patient was discharged with improved neurology at 12 weeks. Conclusions: Perioperative problems after cervical surgery such as breathing difficulty, wound discharge, and worsening of neurology may lead to suspicion of underlying EP due to implant failure. Upper gastrointestinal endoscopy needs to be considered for a prompt diagnosis. Revision spine surgery with treatment of perforation simultaneously and maintenance of enteral nutrition through a percutaneous endoscopic gastrostomy tube with a multispecialty approach is recommended for this potentially life-threatening condition.